Genome organization in cardiomyocytes expressing mutated A-type lamins - Kervella, Marie; Jahier, Maureen; Meli, Albano C.; Muchir, Antoine (Frontiers in Cell and Developmental Biology, 2022)
Cardiomyopathy is a myocardial disorder, in which the heart muscle is structurally and functionally abnormal, often leading to heart failure. Dilated cardiomyopathy is characterized by a compromised left ventricular function and contributes significantly to the heart failure epidemic, which represents a staggering clinical and public health problem worldwide. Gene mutations have been identified in 35% of patients afflicted with dilated cardiomyopathy, of whom pathogenic variants in LMNA, encoding nuclear A-type lamins, are one of the major causative causes. A-type lamins are type V intermediate filament proteins, which are the main components of the nuclear lamina. The nuclear lamina is connected to the cytoskeleton on one side, and to the chromatin on the other side. Among the models proposed to explain how CardioLaminopathy arises, the “chromatin model”, posit an effect of mutated A-type lamins on the 3D genome organization and thus on the transcription activity of tissue-specific genes. Chromatin contacts with the nuclear lamina via specific genomic regions called lamina-associated domains (LADs). These LADs play a role in the chromatin organization and gene expression regulation. This review will focus on the identification of LADs and chromatin remodeling in cardiac cells expressing mutated A-type lamins and will discuss the relevance of these findings in disease.